"Triple Window" Surgical Approach to the Elbow: A Hybrid Exposure. Issue 4 (December 2020) - Kamineni, Srinath; Abbenhaus, Eric; Snowden, Ryan
Abstract : Triceps-off approaches of the elbow detach not only the central tendinous insertion but also the medial and lateral peripheral muscular extensions, which are often replaced by scar tissue instead of functioning contractile muscular tissue when re-attached firmly with suture. These muscular extensions have been shown to be important for terminal elbow extension and may explain why triceps-off approaches have a higher rate of triceps insufficiency in terminal, antigravity elbow extension. Triceps-on approaches of the elbow lead to difficulty accessing the ulna for preparation and insertion of the ulna component of elbow replacements, with malpositioning of the ulna component a common concern. We present an elbow "triple window" surgical approach that preserves the contractile medial and lateral footprints of the triceps, while affording a better in-line access than a pure "triceps-on" approach. This approach only violates 50% of the central tendinous insertion, with the remainder of the central tendon and the medial and lateral muscular extensions preserved.